(A) Product of
and
is:
![(-2x^{3}+x-5)(x^{3}-3x-4)](https://tex.z-dn.net/?f=%28-2x%5E%7B3%7D%2Bx-5%29%28x%5E%7B3%7D-3x-4%29)
![=-2x^{3}(x^{3}-3x-4)+x(x^{3}-3x-4)-5(x^{3}-3x-4)](https://tex.z-dn.net/?f=%3D-2x%5E%7B3%7D%28x%5E%7B3%7D-3x-4%29%2Bx%28x%5E%7B3%7D-3x-4%29-5%28x%5E%7B3%7D-3x-4%29)
![=(-2x^{3})(x^{3})+(-2x^{3})(-3x)+(-2x^{3})(-4)+x(x^{3})+(x)(-3x)+(x)(-4)+(-5)(x^{3})+(-5)(-3x)+(-5)(-4)](https://tex.z-dn.net/?f=%3D%28-2x%5E%7B3%7D%29%28x%5E%7B3%7D%29%2B%28-2x%5E%7B3%7D%29%28-3x%29%2B%28-2x%5E%7B3%7D%29%28-4%29%2Bx%28x%5E%7B3%7D%29%2B%28x%29%28-3x%29%2B%28x%29%28-4%29%2B%28-5%29%28x%5E%7B3%7D%29%2B%28-5%29%28-3x%29%2B%28-5%29%28-4%29)
![=-2x^{6}+6x^{4}+8x^{3}+x^{4}-3x^{2}-4x-5x^{3}+15x+20](https://tex.z-dn.net/?f=%3D-2x%5E%7B6%7D%2B6x%5E%7B4%7D%2B8x%5E%7B3%7D%2Bx%5E%7B4%7D-3x%5E%7B2%7D-4x-5x%5E%7B3%7D%2B15x%2B20)
![=-2x^{6}+6x^{4}+x^{4}+ 8x^{3}-5x^{3}-3x^{2}-4x+15x+20](https://tex.z-dn.net/?f=%3D-2x%5E%7B6%7D%2B6x%5E%7B4%7D%2Bx%5E%7B4%7D%2B%208x%5E%7B3%7D-5x%5E%7B3%7D-3x%5E%7B2%7D-4x%2B15x%2B20)
![=-2x^{6}+7x^{4}+3x^{3}-3x^{2}+11x+20](https://tex.z-dn.net/?f=%3D-2x%5E%7B6%7D%2B7x%5E%7B4%7D%2B3x%5E%7B3%7D-3x%5E%7B2%7D%2B11x%2B20)
(B) Yes.
Product of
and
= Product of
and
because multiplication is commutative.
Commutative Property of multiplication says that a.b = b.a.
Thus, multiplication is same irrespective of the order of two numbers.
Answer:
8 and 7
Step-by-step explanation:
8 -7 = 1
8*7 = 56
I dont lhow the answer tomorrow in the morning I will tell you
Answer: Steps 4 and 5
Step-by-step explanation: